ANALISIS PERAN GURU DALAM MENGATASI KECEMASAN DAN RENDAHNYA MINAT BELAJAR MATEMATIKA SISWA KELAS IV SD - Nur Hasan Salim; Khoirun Nisa' Fitriani; Alna Syakura Failo Sofa; Dian Mustika Anggraini (LPPM Universitas Cipta Mandiri, 2026)
Mathematics is a crucial subject in the elementary school curriculum. However, it is often feared by students due to academic anxiety and low interest in learning. This study aims to explore teachers' contributions in addressing students' anxiety and lack of interest in learning mathematics, particularly among fourth-grade elementary school students, using a comprehensive approach. The study employed a quantitative method, involving 31 fourth-grade elementary school students to assess their levels of anxiety and interest, and 30 teachers who were invited to assess their self-assessments regarding their classroom roles. Data were obtained through a questionnaire using a Likert scale and analyzed using a non-parametric statistical test, namely the Spearman Rank correlation. Findings from the descriptive analysis indicated that most teachers' views on their contributions were in the moderate category (93.3%), and students' anxiety and interest in learning were also predominantly in the moderate category (80.7%). However, the results of the inferential hypothesis test showed a significance value of 0.633, which is higher than the 0.05 level of significance. Therefore, it can be concluded that there is no significant relationship between teachers' roles and the levels of anxiety and interest in learning mathematics in fourth-grade elementary school students. This lack of correlation indicates that a single teacher intervention in the classroom is not strong enough to reduce the psychological barriers that have already formed in students. Therefore, a collaborative strategy is needed that involves the entire education system holistically and individually.